Computer based management information system for water supply organizations - Minnatullah, Khawaja Mohammad; Lohani, B.N.; Nguyen, Cong Thanh; Vigneswaran, S.; Kings Scholsrship, Thailand (Bangkok : Asian Institute of Technology, 1982)
This thesis concerns design and development of a C0mputer Based Management Information System for Water Supply Organizations to aid in the decision making process for program planning purposes. Activities undertaken in this study include, study of the planning process of Water Supply Organizations, identification of the information needs, categorizing information items into functional groups according to the output requirements, design of a coding scheme to accommodate all the projects under water supply program, design of data collection forms and development of user manual to assist in filling the forms correctly. The study also involves the creation of Water Supply Organization data base using the Query-by-Example data base system to investigate its technical feasibility, effectiveness and flexibility in supporting the information system, design and execution of institutional queries to retrieve information from the data base. A limited investigation of the interface use with off-line Watanabe Plotter to generate graphical output is also included in this study.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1982
Keywords: Tanning -- Waste disposal